Daily tonometric curves after cataract surgery. Issue 1 (1st January 2001) - Saccà, S; Marletta, A; Pascotto, A; Barabino, S; Rolando, M; Giannetti, R; Calabria, G
Abstract : AIM: To evaluate daily tonometric curves after cataract surgery in patients with cataract only and in patients with cataract and glaucoma. METHODS: 108 patients scheduled for cataract surgery were randomly allocated to two groups: 57 patients with cataract only (normal) and 51 with cataract and primary open angle glaucoma (POAG). All patients underwent extracapsular cataract extraction (ECCE) (manual technique with long wound), phacoemulsification (automated technique with short wound), or nucleus capture (manual technique with short wound). Intraocular pressure (IOP) was measured by Goldmann tonometry in all patients every 2 hours for 12 hours before the operation and at 1 and 6 months postoperatively. RESULTS: 79 patients completed the 6 month examination. ECCE resulted in greater reductions in IOP than the other procedures (ECCE: 27% and 36% in normal patients and those with POAG, respectively; nucleus capture: 20% and 31%, respectively; phacoemulsification: 19% and 22%, respectively). The fluctuations in IOP before and after surgery were not statistically significant. CONCLUSION: Cataract surgery in normal patients reduces IOP but does not eliminate fluctuations which are directly proportional to the IOP value and result partly from circadian rhythms. This important finding might influence our approach to treatment of patients with glaucoma.